Survival Following Surgery with or without Adjuvant Chemotherapy for Stage I–IIIA Non-Small Cell Lung Cancer: An East Asian Population-Based Study - Lin, Zhong-Zhe (AlphaMed Press, 2012)
BACKGROUND. Asian ethnicity is associated with a distinct molecular etiology, treatment response, and survival outcome among patients with non-small cell lung cancer (NSCLC). This study examines the survival impact of platinum-based adjuvant chemotherapy for Asian patients with stage I–IIIA NSCLC. METHODS. This study recruited patients aged ≥18 years with histologically proven stage IA–IIIA NSCLC registered in the Taiwan Cancer Registry database in January 2004 to December 2007. Platinum-containing adjuvant chemotherapy had to be started within 90 days of the primary surgery. Kaplan–Meier survival curves, log-rank tests, and the Cox proportional hazards regression model were used to assess the influence of various risk factors on survival time. RESULTS. This study included 2,231 patients with stage IA–IIIA NSCLC who underwent primary surgery with a clear surgical margin. The percentages of all causes of death were significantly lower for the chemotherapy group for both stage II and stage IIIA patients. Multivariate analysis identified platinum-based adjuvant chemotherapy as an independent prognostic factor for the overall survival outcome of stage II (hazard ratio [HR], 0.61; 95% confidence interval [CI], 0.39–0.94; p = .024) and IIIA (HR, 0.71; 95% CI, 0.52–0.96; p = .029) patients. Among these patients, those who received adjuvant chemotherapy had a superior overall survival outcome for both genders, for the subgroup of patients aged ≥70 years, and for those with adenocarcinoma. CONCLUSION. Platinum-based adjuvant chemotherapy should be considered in the treatment plan for Asian patients with resected stage II and stage IIIA NSCLC.